2020
DOI: 10.12965/jer.2040044.022
|View full text |Cite
|
Sign up to set email alerts
|

When will pulmonary function recover after rib fracture?

Abstract: Rib fracture is almost recovered with conservative management including oral medication. Pain is easily controlled with medication, but physiologic function is not readily evaluated. This study is aimed to investigate the factors influencing to recovery of pulmonary function test (PFT) and changes according to times after rib fracture. From August 2015 to January 2018, medical records of patients with rib fracture were reviewed retrospectively. Factors may influencing to recovery of PFT (age, chronic obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…It has been proved in our previous studies that the fractures of multiple continuous ribs may cause severe impairment of pulmonary function (PF). [10][11]Meanwhile, it has also been proved that the internal xation of rib fracture can signi cantly improve the impaired PF in the acute phase, which has also been con rmed by a great number of studies [12][13][14]. In this study, we con rmed that costal cartilage fractures may also cause the impaired integrity of thoracic cage.…”
Section: Resultssupporting
confidence: 67%
“…It has been proved in our previous studies that the fractures of multiple continuous ribs may cause severe impairment of pulmonary function (PF). [10][11]Meanwhile, it has also been proved that the internal xation of rib fracture can signi cantly improve the impaired PF in the acute phase, which has also been con rmed by a great number of studies [12][13][14]. In this study, we con rmed that costal cartilage fractures may also cause the impaired integrity of thoracic cage.…”
Section: Resultssupporting
confidence: 67%
“…19 However, it is not a determinant of the length of the post-rib fracture medical rehabilitation program, which is determined by the presence or absence of comorbid Chronic Obstructive Pulmonary Disease (COPD) before the occurrence of thoracic trauma. 20 Thoracic trauma was not accompanied by bilateral rib fractures in this study. This is different from a study in the United States which reported that 120 patients out of 385 cases of thoracic trauma experienced bilateral rib fractures.…”
Section: Discussionmentioning
confidence: 45%
“…The improvement of FEV1 was also higher in good compliance patients, although there was no significant difference. Regular performance of lung expansion exercise and pulmonary rehabilitation showed impact on final PFT parameters in rib fractures patients [8,30]. Additionally, the frequency of using this spirometry system has positive effects on patients' rehabilitation.…”
Section: Discussionmentioning
confidence: 92%